2019
DOI: 10.1021/acsapm.9b01000
|View full text |Cite
|
Sign up to set email alerts
|

Hyper-Cross-Linked Polymers for the Capture of Aromatic Volatile Compounds

Abstract: Hyper-cross-linked porous polymers (HCPs) are proposed as sorbents for the removal of aromatic volatile pollutants by using toluene as a representative of the BTX family. The hierarchical (micro and meso) porous architecture of the HCPs has been established by N2 physisorption at 77 K while the toluene adsorption capacities were determined by volumetric adsorption at 308 K. The HCPs display very high toluene uptakes, reaching adsorption capacities as high as 154% in weight for the polymer obtained with a tetra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 48 publications
2
33
0
Order By: Relevance
“…Towards higher values of P/P 0 a gradual increase in the amount of adsorbed nitrogen is observed indicating the filling of mesopores in the range between 0.45 and 0.8 P/P 0 . Open hysteresis loops for both materials are observed for the whole desorption branch, which is consistent with swelling effects of the polymeric network, due to gas sorption [36,37]. The non-reversible desorption at low relative pressures indicates that N 2 could either be trapped in pockets or free volume elements with a size comparable to that of the N 2 molecule, or swelling of ABT is locking some of the pockets or free volume elements on the time scale of the experiments, or in combination.…”
Section: N 2 Physisorption Analysissupporting
confidence: 72%
See 3 more Smart Citations
“…Towards higher values of P/P 0 a gradual increase in the amount of adsorbed nitrogen is observed indicating the filling of mesopores in the range between 0.45 and 0.8 P/P 0 . Open hysteresis loops for both materials are observed for the whole desorption branch, which is consistent with swelling effects of the polymeric network, due to gas sorption [36,37]. The non-reversible desorption at low relative pressures indicates that N 2 could either be trapped in pockets or free volume elements with a size comparable to that of the N 2 molecule, or swelling of ABT is locking some of the pockets or free volume elements on the time scale of the experiments, or in combination.…”
Section: N 2 Physisorption Analysissupporting
confidence: 72%
“…Between 3000 and 2800 cm −1 , the signals of aliphatic C-H stretching vibrations are found. In particular, the band at 2965 cm −1 is assigned to the C-H asymmetric stretching mode of methyl groups [ 37 , 39 , 40 ] while the band at 2922 cm −1 is assigned to the asymmetric stretching mode of the -CH 2 - group [ 39 , 40 ]. The corresponding symmetric stretching vibrations are found at 2870 cm −1 for the methyl group and at 2845 cm −1 for the methylene group [ 37 , 39 , 40 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The toluene adsorption properties of different porous silicas (i.e., fumed silica, SBA-15 and commercial MCM-41) have been recently reported by our group [ 16 ] and we have shown that the porous architecture of different silicas have an important effect on the final adsorption properties. In the same conditions, we also tested the adsorption behaviour of siliceous zeolites and hypercross-linked polymers [ 17 ]. We derived that whereas siliceous zeolite adsorbs 21 Q% of toluene, HyperCross-linked Polymers (HCP S ) with flexible structures are able to adsorb more than 140 Q% of toluene.…”
Section: Introductionmentioning
confidence: 99%